2019
DOI: 10.3847/1538-4357/ab0c06
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of X-Ray Tails of Early-type Galaxies and Subclusters in Galaxy Clusters: Slingshot Tails versus Ram Pressure Stripped Tails

Abstract: We show that there is a new class of gas tails -slingshot tails -which form as a subhalo (i.e. a subcluster or early-type cluster galaxy) moves away from the cluster center towards the apocenter of its orbit. These tails can point perpendicular or even opposite to the subhalo direction of motion, not tracing the recent orbital path. Thus, the observed tail direction can be misleading, and we caution against naive conclusions regarding the subhalo's direction of motion based on the tail direction. A head-tail m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 52 publications
5
47
0
Order By: Relevance
“…-The overall morphology is consistent with the post-merger scenario described in Lyskova et al (2019); Sheardown et al (2019); Zhang et al (2019), in which the NGC 4839 group has passed through the Coma cluster from the NE direction, reached the apocenter, and is now starting its second infall toward the main cluster; -A faint X-ray bridge connecting the NGC 4839 with the main cluster provides convincing proof that the group has already crossed the Coma core; -X-ray spectral analysis robustly classifies some of the most prominent structures as shocks or contact discontinuities.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…-The overall morphology is consistent with the post-merger scenario described in Lyskova et al (2019); Sheardown et al (2019); Zhang et al (2019), in which the NGC 4839 group has passed through the Coma cluster from the NE direction, reached the apocenter, and is now starting its second infall toward the main cluster; -A faint X-ray bridge connecting the NGC 4839 with the main cluster provides convincing proof that the group has already crossed the Coma core; -X-ray spectral analysis robustly classifies some of the most prominent structures as shocks or contact discontinuities.…”
Section: Discussionsupporting
confidence: 83%
“…Firstly, we outline the broad brush scenario, originally mentioned in Burns et al (1994) and Biviano et al (1996) and discussed in detail in Lyskova et al (2019); Sheardown et al (2019); Zhang et al (2019). In this scenario, the NGC 4839 group was initially moving from the NE along the general direction of the Coma-A1367 filament.…”
Section: Broad Brush Merger Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Although this finding is in clear disagreement with the scenario of first infall for the NGC 4839 group, it is actually very consistent with recently proposed analyses (e.g. Sheardown et al 2019;Lyskova et al 2019) which advocate for a post-merger scenario for NGC 4839, where the galaxy has crossed the cluster core already once and is now coming out the other side. Quite interestingly, in this case the infall direction for NGC4839 would be the NE corner of the cluster, where DisPerSEfinds a quite significant filament.…”
Section: Indirect Confirmation Of the First Generation Filamentssupporting
confidence: 72%
“…Gill et al (2005) found that half of the galaxies in the infall region have already orbited through the main cluster. M49 may have just turned around at its apocenter and started to accelerate towards M87, forming a cold front and leaving behind a slingshot tail (Sheardown et al 2019). Extended X-ray mapping of the Virgo cluster reveals sloshing fronts in multiple directions and over a large span of radii, including two large scale sloshing fronts at r = 200-300 kpc (Simionescu et al 2017).…”
Section: The Group Atmosphere and Merger Historymentioning
confidence: 99%